Optimisation of rice bran hydrolyzation by xylanase for Xylooligosaccharide production - Nhung, Tran Thi; Thu Phuong, Pham Thi; Huong, Nguyen Thuy; Mai Phuong, Nguyen Thi (Academia Journal of Biology, 2013)
Rice bran is a subsidy product of rice processing. It is rich in carbohydrate, especially xylan therefore, has being used for production of soluble fiber oligosaccharide including xylooligosaccharides (XOS). XOS has been proven to be fermented by beneficial bacteria Bifidobacteria and Lactobacillus in colon. The market for XOS is increasing rapidly due to its advantages in biological and technological properties compared to other common oligosaccharides, such as fructooligosaccharide (FOS) or galactooligosaccharide (GOS). XOS can be produced from rice bran by using either chemical or enzymatic hydrolyzation technologies. The hydrolyzation using β-1,4-xylanase is commonly used to produce XOS from rice bran. However, an appropriate technology for XOS production from rice bran with high purity and food safe in Vietnam is still badly needed. This paper presents new research results on XOS production from rice bran by using a multienzymatic and environmental friendly technology. A XOS preparation with purity level of 81.4% has been obtained by hydrolyzing protease and α-amylase pretreated rice bran with 0.6% commercial Ultraflo L xylanase from Novozyme at pH 7.0 and 50oC in 100 mM phosphate buffer for 15 hours. This is an appropriate technology for XOS production from rice bran in Vietnam.